NOTARY'S RESPONSIBILITY FOR THE SETTLEMENT OF CLAIMS BY HEIRS WHO WERE NOT INCLUDED IN THE DISTRIBUTION OF INHERITANCE RIGHTS - Dina Rahmawati; Budi Parmono; Sunardi (SOSIOEDUKASI, 2025)
This study seeks to scrutinize the liability of notaries in relation to legal actions initiated by heirs excluded from the allocation of inheritance rights, as well as to assess the forms of legal protection available to the affected parties through normative legal inquiry. Employing a normative juridical methodology with a doctrinal literature approach, the research examines notarial liability in cases involving claims by omitted heirs in inheritance distribution. The analysis is conducted in a descriptive–analytical manner, drawing upon primary, secondary, and tertiary legal sources to interpret prevailing legal norms and formulate conclusions. The findings indicate that (1) notarial liability arising from lawsuits filed by heirs excluded from the certificate of inheritance rights manifests as responsibility for deeds executed by the notary when errors result in losses, thereby constituting an unlawful act pursuant to Articles 1365 and 1366 of the Civil Code. Consequently, such deeds may be declared null and void, and the notary may incur civil liability in the form of compensation, reimbursement of expenses, and interest, in addition to administrative sanctions ranging from written admonitions to removal from office. Furthermore, legal protection for heirs not recorded in the inheritance deed may be pursued through both preventive and repressive legal mechanisms.